Collegial administrative will (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
The collegiate model ("collegium") wants to respond to a horizontal formation of acts and concurrence of wills, seeking a deliberation over points of view from the members of the body; from which a peculiar legal regime is derived, because single-person bodies manifest its will by its sole owner, whereas collegial bodies have a procedure that must be followed to achieve evidence of the "collegial administrative will"
Keywords: Administrative act; Collegiate; Administrative body; Collegial body; Secretary